2021
DOI: 10.1093/jmammal/gyab125
|View full text |Cite
|
Sign up to set email alerts
|

Role of microhabitat and temporal activity in facilitating coexistence of endemic carnivores on the California Channel Islands

Abstract: Most extinctions worldwide have occurred on islands, primarily due to interactions with exotic species, but rarely due to interactions among endemic species. This potential exists on two of the California Channel Islands, Santa Cruz and Santa Rosa, as endemic island spotted skunks (Spilogale gracilis amphiala) appear to have rapidly declined to rarity, possibly due to interference competition with endemic island foxes (Urocyon littoralis). Niche partitioning is expected in response to interference competition;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…However, genus‐level analyses consistently returned two genera within Actinobacteria ( Arcanobacterium and Mobiluncus ) as significantly more abundant in island spotted skunks compared to island foxes across both islands. As Actinobacteria is one of the most abundant bacterial taxa in soils (Lewin et al., 2016 ), this may reflect habitat use by island spotted skunks, which spend more time in ravines or covered places while foraging for soil‐dwelling prey (Bolas, Sollmann, et al., 2022 ; Crooks & Van Vuren, 1995 ). We therefore posit that the increased presence of certain bacterial classes in island foxes and island spotted skunks may derive from eco‐evolutionary differences in their population histories, diets, and preferred habitat types, as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, genus‐level analyses consistently returned two genera within Actinobacteria ( Arcanobacterium and Mobiluncus ) as significantly more abundant in island spotted skunks compared to island foxes across both islands. As Actinobacteria is one of the most abundant bacterial taxa in soils (Lewin et al., 2016 ), this may reflect habitat use by island spotted skunks, which spend more time in ravines or covered places while foraging for soil‐dwelling prey (Bolas, Sollmann, et al., 2022 ; Crooks & Van Vuren, 1995 ). We therefore posit that the increased presence of certain bacterial classes in island foxes and island spotted skunks may derive from eco‐evolutionary differences in their population histories, diets, and preferred habitat types, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, island spotted skunks tend to be more specialized in their habitat use, while island foxes utilize all areas across the island (Crooks & Van Vuren, 1995 ). There may be further differences in microhabitat use, with island spotted skunks often found in areas with ground‐level cover in the form of rugged terrain or dense vegetation (Bolas, Sollmann, et al., 2022 ; Gagorik, 2020 ). Regarding temporal dynamics, island spotted skunks are largely nocturnal, whereas island foxes are cathemeral (active during both the day and night; Bolas, Sollmann, et al., 2022 ; Zhang et al., 2022 ), with differing degrees of seasonality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study system, because spotted skunks uniquely showed sensitivity to each of the four hypothesized drivers of carnivore occurrence, we suggest that spotted skunks are likely the ideal sentinel species in this study area, and likely more broadly across their range. Indeed, recent studies on spotted skunks have shown their utility in advancing our understanding of disease outbreaks (Harris et al, 2021), historical climate and land use change (Cheeseman et al, 2021a(Cheeseman et al, , 2021b, changing predator community dynamics (Bolas et al, 2022), and food web linkages between aquatic, terrestrial and arboreal systems (Tosa et al, 2023). Such sensitivities by small carnivores are not unique to our system and are likely represented in small carnivores in ecosystems globally (Do Linh San et al, 2022;Marneweck, Allen, et al, 2022).…”
Section: F I G U R Ementioning
confidence: 99%
“…Since the island fox is the most abundant (and often the only) midsized mammalian omnivore on the Channel Islands, it may often be the sole mammalian agent of seed dispersal. However, much of the research on the potential ecological roles of the island fox has focused on predation and competition (Roemer et al 2002, Phillips et al 2007, Coonan et al 2010a, 2010b, Orrock 2010, Orrock and Fletcher 2014, Bolas et al 2022. Despite the potential for island foxes to provide important seed dispersal services, it is still unclear whether island foxes disperse the seeds of island plants.…”
mentioning
confidence: 99%